Nature vs nurture : an experimental study on intergenerational transmission of risk preference - Ong, Shi Ting (2019)
This paper reviews empirically the extent to which parents shape the risk attitudes of their children through simple decision-making tasks. Utilising the Holt-Laury’s Task Experiment, we conducted a novel experiment on 201 pairs of parent-child subjects by introducing a separation intervention as our treatment. We targeted young children of ages from 3 to 8 years old. Our findings support the intergenerational transmission of risk attitude; they show that the risk behaviour of parents is statistically significant and positively correlated to their children. Our results also suggest that there is no significant effect of risk preferences of parents on children when they conduct the experiment in different rooms. This highlights the importance of parental involvement in harnessing children’s risk-taking impulses, and vitally suggests that the nurture from parents is critical in forming the risk preferences of their children.